STUDI KELAYAKAN FINANSIAL PENGOLAHAN LIMBAH CAIR TAPIOKA SEBAGAI NATA DE CASSAVA - Dianawati Dianawati; Widowati Widowati (BUANA SAINS, 2009)
Tapioca industries produced liquid waste containing substantial amount of starch that can be used as a source of carbon. Considering its relatively high carbon content, the liquid waste of tapioca production can be used as a raw material of nata de cassava. This study was aimed to elucidate financial feasibility of nata de cassava production at PT Sumber Timur, Dampit, Malang. The financial feasibility parameters included Break Even Point, Payback Period, RCR, Net BCR, Net Present Value and Internal Rate of Return. The information and assumptions for financial analysis were: liquid waste of tapioca was about 500 l/day, 1 kg cassava pulp produced 8,27 l liquid waste, from 500 kg fermented liquid waste of tapioca, taken 50 kg for starter, rendement = 99,54%, lifetime of the factory was 10 years, Price was increased 4%/ years started from third years, product was sold 100% from 1st - 10th years, production cost was increased 4%/ years started from third years. Results of this study indicated that production capacity for 1 year was 179.160,00 kg, the price was Rp. 1.112,21/ kg, production of nata de cassava from liquid waste of tapioca was financially feasible with NPV (18%)=Rp. 130.082.978,55, BEP = 26.015,29 kg or Rp. 28.934.382,83 or 15%; IRR 37%, Payback Period 4,14 years, Net BCR 1,02 and RCR 1,56